Сини київської князівни Доброніги-Марії († 1087) на престолі Польщі: генеалогічний та культурний аспекти - Ясинецька, О. (Краєзнавство, 2018)
У статті проаналізовано особливості родоводу синів київської князівни Доброніги-Марії – правителів Польщі Болеслава ІІ Щедрого (бл. 1042 ‒ п. 1081) та Владислава І Германа (бл. 1044 ‒ 1102), їх
дружин та нащадків. Зʼясовано особливості їх життя та діяльності, а також визначено їх роль у
культурному розвитку Давньопольської держави, зокрема у сфері церковного будівництва. The Article analyses the peculiarities of genealogy of two sons of Kyivan Princess Dobriniga-Maria –
Polish state rulers – Bolesław II the Generous (the Bold; circa 1042 – after 1081) and Władisław I Herman
(circa 1044–1102). The research considers the circumstances of matrimonial alliance between king of Poland
Bolesław II and Ruthenian princess Vysheslava (c. 1047 – after 1089). Genealogy of Bolesław’s wife, Ruthenian
princess Vysheslava is deduced as a granddaughter of Yaroslav the Wise. The existed genealogical hypotheses
of her origin are considered. The arguments in favor of her origin from the family of Przemyśl dukes – the descendants
of Volodymyr Yaroslavych (1020‒1052) are adduced. The data concerning the only successor of the
royal couple – Mieszko (circa 1042–after 1081) and his dynastic marriage with Ruthenian princess are given.
The peculiarities of the life and activities of the Polish-Rus royal couples are ascertained, as well as their role
in cultural development of Poland in 11th‒12th centuries. The monuments of sacred architecture founded or renewed
by Bolesław II, Władisław I Herman and their families are designated. The research substantiates the
existence of active dynastic relations between Poland and Kyivan Rus in the 11th‒12th centuries as an important
factor of international and intercultural cooperation. В статье проанализировано обстоятельства родовода сыновей киевской княжны Добронеги-Марии –
правителей Польши Болеслава ІІ Щедрого (ок. 1042‒ п. 1081) и Владислава І Германа (ок. 1044 ‒102), их
жен и потомков. Определены особенности их жизни и деятельности, а также их роли в культурном
развитии Древнепольского государства, в частности в сфере церковного строительства.